An Evaluation of Internet Addiction and Its Related Factors among the Students of Yazd University of medical Science in 2016 - Nasim Namiranian; Seied Saman Mansouri; Mohammad Shafiee (Shahid Sadoughi University of Medical Sciences, 2020)
Introduction: The Internet is one of the most advanced human achievements that encompasses a wide and unbroken network of multiple links. The vast Internet usage and appetite has led to the emergence of a phenomenon called Internet addiction in recent years; As Internet usage has multiplied in recent decades and its users have grown exponentially, the Internet has become a necessity for life. Considering the increase in the rate of Internet addiction, we tried to investigate the rate of internet addiction among medical students of Shahid Sadoughi University of Medical Sciences in Yazd in 1395.   Materials & Methods: This analytic-cross-sectional study was performed on 350 students of Shahid Sadoughi University of Medical Sciences in Yazd. The sampling was random sampling. The data collection tool was a demographic questionnaire and Yangchr('39')s Internet addiction inventory. The questionnaire contains 20 questions, according to which the person is placed in one of four classes: normal, mild, moderate and severe. After collecting the data, the data were entered into SPSS 16 software and analyzed using Chi-square and independent t tests.   Results: The results of the study showed that out of 350, 183 (52.3%) were female and 167 (47.7%) were male. According to Internet addiction, students were 65% normal, 33.3% border lip And 1.7% were addicted to the Internet. The results also showed that there was a significant statistical relationship between the prevalence of internet addiction among students and sex, smoking and registration in cyberspace, and there was no significant statistical relationship between the prevalence of internet addiction and marital status, place of residence and birth place.   Conclusion:. Given the importance of the field of medicine and its connection with the lives of people, Internet addiction is at all possible thoughtful among medical students and should be taken by adopting programs such as holding workshops on the advantages and disadvantages of using the Internet and its subsequent consequences, Increased student awareness of the dangers of internet addiction.